Transferencia de los recursos públicos y su relación con la ejecución del gasto público en la Universidad Nacional de la Amazonía Peruana, periodo 2018 – 2022 - Rengifo Flores, Xiomy Sibelly (2024)
Public sector entities or institutions require the necessary means to fulfill their public purpose, which is why they receive funds through transfers of public resources from the central government, so that they can develop their planned activities over a given period, and also ensure that they have the resources to finance the execution of public expenditure, in accordance with the objectives and targets that were established. The present study includes the conduct of an investigation called "Transfer of public resources and its relationship with the execution of public spending at the National University of the Peruvian Amazon, period 2018 - 2022", and its implementation focused primarily on determining the relationship between the transfer of public resources and the execution of public expenditure, whose evaluation time or space covered a period of five (5) years, where it is necessary that, to continue with the development of the same had to use several techniques as the survey, selective review, analysis, tabulation and calculation, and for the collection of information was used the data record sheet, as methodology had in quantitative approach, descriptive level - correlational and nonexperimental - longitudinal design. The results indicate a considerable positive (regular) relationship, which is based on the value obtained by means of Spearman’s Rho correlation coefficient, which was 0.417.